Manajemen Kinerja Berbasis Budaya Religius Dalam Meningkatkan Profesionalisme Guru Di Madrasah Ibtidaiyah Nurul Ihsan Sarang Burung Kabupaten Muaro Jambi - Harianto; Dwi Bhakti Indri (Suria Academic Press, 2025)
Religious culture management is crucial, especially in the world of education. Where management based on religious culture, which essentially guides, directs, and shows the path that is pleasing to Allah SWT, has an important role in improving teacher professionalism. This study aims to find out; 1) How performance management based on religious culture improves teacher professionalism at Madrasah Ibtidaiyah Nurul Ihsan Sarang Burung Muaro Jambi, 2) What are the roles of performance management based on religious culture in improving teacher professionalism at Madrasah Ibtidaiyah Nurul Ihsan Sarang Burung Muaro Jambi, 3) What are the inhibiting and supporting factors in the implementation of performance management based on religious culture in improving teacher professionalism at Madrasah Ibtidaiyah Nurul Ihsan Sarang Burung Muaro Jambi. Using qualitative research methods, data were obtained through observation, interviews, and documentation. The researcher found that; 1) Performance management based on religious culture is the Application of Integration of Religious Values, habituation, and Spiritual Guidance, Teacher Competency Development, evaluation, and Appreciation, 2) Inhibiting factors for the head of the madrasah are Limited Human Resources, Limited Activity Time, Differences of Opinion in Decision Making. The supporting factors are; Headmaster's Commitment, Competency Development. 3) While the efforts made by the head of the madrasah include; Developing Spiritual Guidance Programs, Improving the Quality of Worship, Developing an Islamic School Environment.